Word of caution on adding hemiarch replacement to a proximal aortic aneurysm repair: long-term outcome analysis of over 1, 000 patients. (14th October 2021) - Pearsall, C P; Blitzer, D B; Zhao, Y Z; Yamabe, T Y; Kim, I K; Bethancourt, C B; Hu, D H; Bergsohn, J B; Kurlanksy, P K; George, I G; Smith, C S; Takayama, H T
Abstract: Background: There is no consensus nor recommendation for the surgical management of a minimally dilated adjacent aortic segment, such as the proximal aortic arch, at the time of proximal aortic aneurysm repair. Consequently, clinical equipoise exists regarding whether to extend the proximal aortic aneurysm repair to include the proximal aortic arch, by performing a hemiarch replacement, to mitigate the future risk of aortic aneurysm-related events in the proximal aortic arch. We hypothesized that additional hemiarch replacement to excise a non- or minimally aneurysmal proximal aortic arch does not have clinical benefit in patients undergoing proximal aortic aneurysm repair. Purpose: To compare the long-term survival and freedom from aortic-arch reoperation in patients undergoing proximal aortic aneurysm repair with and without additional hemiarch replacement. Methods: A retrospective review was performed of all patients undergoing proximal aortic aneurysm repair at our Aortic Center between 2005 and 2019. Inclusion criteria included all patients with a diagnosed root or ascending aortic aneurysm undergoing root or ascending aortic replacement with or without hemiarch replacement. Exclusion criteria were Age <18 years, presence of aortic arch diameter ≥4.5 cm, type A aortic dissection, previous ascending aortic replacement, aneurysm rupture, and endocarditis. A total of 1132 patients (hemiarch =307) met inclusion criteria. Propensity score matching in a 2:1 ratio (573 non-hemiarch: 288 hemiarch) on 19 baseline characteristics was performed. The median follow-up was 29.7 months (range: 0.1–153.8 months). Results: Hemiarch patients had a significantly lower 10-year survival rate (86.7%; 95% CI, 79.2–94.8 in non-hemiarch vs 81.9%; 95% CI, 75.9–88.3 in hemiarch; P=0.005). There was no significant difference in 10- year cumulative incidence of aortic-arch reintervention (0.7%; 95% CI, 0.3–1.9 in non-hemiarch vs 0.69%; 95% CI, 0.17–2.75 in hemiarch; P=0.99). Hemiarch patients had higher rates of in-hospital mortality (1% in non-hemiarch vs 4% in hemiarch; P<0.001), stroke (3% in non-hemiarch vs 6% in hemiarch; P=0.047), reoperation for bleeding (4% in non-hemiarch vs 9% in hemiarch; P=0.011), and respiratory failure (7% in non-hemiarch vs 13% in hemiarch; P=0.006). In multivariable COX analysis, hemiarch replacement was significantly associated with long-term mortality (HR, 2.19; 95% CI, 1.36–3.55; P<.001) but not with aortic-arch reintervention (HR, 1.14; 95% CI, 0.63–2.10, P=0.66). Conclusions: Proximal aortic aneurysm repair with additional hemiarch was associated with higher mortality without a decrease in aortic-arch reintervention rates compared to isolated proximal aortic aneurysm repair. Furthermore, aortic arch reintervention rate was extremely low. These data call for caution in adding hemiarch replacement at the time of proximal aortic aneurysm repair. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Institute of Heath (NIH) 5T35HL007616-40 grant